Analysis of Internal Factors for the Worm Case on the Nutritional Status of Children in Roof Tile Craftsmen Areas - Lestari, Nurarifah Wiji; Woro Kasmini Handayani, Oktia; Rini Indriyanti, Dyah (Universitas Negeri Semarang, 2020)
Worm is an infectious disease caused by parasites in the form of worms. Worm infections that are transmitted through soil or commonly referred to as Soil Transmitted Helminths (STH) types, namely Ascaris lumbricoides, Trichuris trichuira, Ancylostoma duodenale and Necator americanus. The purpose of this study was to analyze internal factors related to the case of worms and have an impact on the nutritional status of children in the roof tile craftsmen area in Karanggeneng Village, Boyolali Regency. This research is a quantitative study, with a cross sectional approach. The research sample was 119 respondents obtained by simple random sampling technique. Data collection techniques are interviews, observation and laboratory tests. Data analysis in this study used descriptive statistical tests and linear regression. The results of research in the roof tile craftsmen area of Karanggeneng Village, Boyolali Regency, showed that there was a relationship between the variables of hand washing (p = 0.000), cutting nails (p = 0.000), defecation habits (p = 0.000) on the case of worms. This study also showed that the variable eating habits (p = 0.040) and the case of worms were related to the nutritional status of children (p = 0.007).